Iron chelators as a therapeutic option for Alzheimer’s disease—A mini-review - Schreiner, Oliver Daniel; Schreiner, Thomas Gabriel (Frontiers in Aging, 2023)
Neurodegenerative disorders, particularly Alzheimer’s disease (AD), remain a great challenge regarding the finding of effective treatment, one main reason being the incomplete understanding of their etiology. With many intensely debated hypotheses, a newer approach based on the impact of iron imbalance in sustaining neurodegeneration in the central nervous system becomes increasingly popular. Altered iron homeostasis leads to increased iron accumulation in specific brain areas, explaining the clinical picture of AD patients. Moreover, growing evidence sustains the significant impact of iron metabolism in relationship to other pathological processes encountered in the AD-affected brain, such as the amyloidogenic pathway, chronic inflammation, or oxidative stress. In this context, this mini-review aims to summarize the novel data from the continuously expanding literature on this topic in a didactic manner. Thus, in the first part, the authors briefly highlight the most relevant aspects related to iron absorption, transport, regulation, and elimination at the cerebral level, focusing on the role of the blood-brain barrier and the newer concept of ferroptosis. Subsequently, currently available iron chelation therapies are discussed, including an overview of the most relevant clinical trials on this topic. In the final part, based on the latest results from in vitro and in vivo studies, new research directions are suggested to enhance the development of effective antidementia therapies.